Quantitative methods for business : custom for Southern Methodist University - Anderson; Sweeney; Williams (Mason, Ohio : Cencage Learning, 2009)
"This book is concerned with the use of quantitative methods to assist in decision making. It emphasizes not the methods themselves, but rather how they can contribute to better decisions."
1. Introduction -- 2. Introduction to probability -- 3. Probability distributions -- 4. Decision analysis -- 5. Forecasting -- 6. Introduction to linear programming -- 8. Linear programming: sensitivity analysis and interpretation of solution -- 9. Linear programming applications in marketing, finance, and operations management -- 10. Distribution and network models -- 11. Project scheduling: PERT/CPM -- 12. Inventory models -- 13. Waiting line models -- 14. Simulation -- Appendix A -- Appendix B -- Appendix C -- Appendix D -- Appendix E -- Appendix F -- Appendix G -- Index.
Includes index.
Keywords: MANAGEMENT SCIENCE